(untitled) (Research, Society and Development, 2023)
Pedagogical coordination can be carried out by a qualified teacher, with a degree in pedagogy, or at postgraduate level, as indicated in LDB nº 9394/1996. Therefore, the present article, questioning who is the pedagogical coordinator in the professional education of the education network of the State of Rio Grande do Norte, aims to identify who is responsible for the exercise of this function in the network. With a qualitative approach, the methodology adopted was a documentary analysis of the aforementioned LDB, as well as of Complementary Law nº. 585/2016, which provides for the democratic and participatory management of the State Educational Network, as well as of Law nº. 10.049 /2016, approving the National Education Plan (2015-2025), among others. This work sought to show how the implementation and effectiveness of PE in the education system of this State have taken place, as well as on which the professional and pedagogical coordination is based within the framework of the history of the pedagogy course in its regulations, placing the pedagogical coordination in the national education network, which is responsible for exercise this function and its intended powers. The analysis of local legislation has shown that pedagogical coordination is a position of trust appointed by the school director. Moreover, we do not observe, among what is conceived of this coordination and the various attributions proposed by the Law, the particularity of a formation and an attribution to and for the performance in PE, being sometimes treated in a subsumed with the generic term "education professionals".